Longitudinal patterns of postpartum body mass index and their impact on cardiometabolic and renal risk among women with prior gestational diabetes: a prospective cohort analysis - Nie, Zicheng; Zhao, Wenbo; Jing, Quanmin (Frontiers in Endocrinology, 2025)
BackgroundWomen with a history of gestational diabetes mellitus (GDM) face a heightened long-term risk of developing interconnected cardiovascular, renal, and metabolic (CKM) conditions. Although postpartum weight management presents a critical opportunity for intervention, the behavioral and psychosocial pathways linking body mass index (BMI) trajectories after childbirth to CKM progression remain poorly defined.MethodsThis prospective cohort study followed 1,268 women with prior GDM, enrolled within six months after delivery and tracked over a median period of 6.5 years. Latent class growth modeling was employed to identify distinct patterns of postpartum BMI change. Psychosocial stress and sleep quality were assessed using standardized instruments at baseline and at the three-year follow-up. Incident CKM outcomes—including hypertension, type 2 diabetes mellitus (T2DM), and reduced estimated glomerular filtration rate (eGFR)—were verified through clinical records. Multivariable Cox regression was used to evaluate the relationship between BMI trajectories and CKM risk, while parallel mediation models quantified the indirect contributions of stress and sleep disturbances.ResultsParticipants with persistently high or progressively increasing BMI patterns experienced significantly elevated risks of CKM outcomes (hazard ratios ranging from 1.35 to 2.10, all p < 0.01), compared to those with stable or declining BMI. Mediation analysis revealed that psychosocial stress and impaired sleep jointly mediated 12.3% (95% CI: 0.02–0.09 for stress; 0.00–0.07 for sleep) of the association in the gradual increase group and 18.5% (95% CI: 0.04–0.13 for stress; 0.02–0.09 for sleep) in the persistently high group, indicating statistically significant indirect effects.ConclusionsIn women with a history of GDM, adverse postpartum BMI trajectories are strongly associated with increased long-term risk of CKM morbidity, with behavioral factors such as stress and sleep quality serving as partial mediators.